Pengaruh Perhatian Orang Tua dan Pendidikan Pesantren terhadap Pembentukan Karakter Santri di Pondok Pesantren Al Manar Semarang - Insani, Anisa Nurul Santy Nur; Arbarini, Mintarsih (AS-SABIQUN, 2025)
The phenomenon of moral degradation among adolescents in the digital era necessitates effective intervention through structured educational institutions and family collaboration. This study aims to examine and analyze the influence of parental attention and Islamic boarding school (pesantren) education on character formation among students at Pondok Pesantren Al Manar, Semarang. A descriptive quantitative method was employed using purposive sampling, involving 50 students aged 17–18 who had resided in the pesantren for at least two years. Data were collected using a validated questionnaire (Cronbach's Alpha > 0.70), covering dimensions of parental attention (emotional, spiritual, material support, and communication), pesantren education (habituation, exemplary behavior, controlled environment, and integrated curriculum), and character formation (religious values, nationalism, integrity, independence, and mutual cooperation). Data were analyzed using Pearson correlation and multicollinearity tests with SPSS. The results show a strong positive correlation between pesantren education and character formation (r = 0.651; p < 0.01), and a moderate positive correlation between parental attention and character formation (r = 0.303; p < 0.05). Simultaneous analysis indicates a significant synergistic relationship between the two independent variables and character formation (r = 0.435; p < 0.01), with a tolerance value of 0.811 and VIF of 1.233, indicating no multicollinearity. In conclusion, pesantren education plays a dominant role in shaping character through a comprehensive and structured approach, while parental attention strengthens the students’ psychological and emotional foundation. The synergy between family and pesantren institutions creates an integrated and effective character education ecosystem capable of addressing adolescent moral challenges in the digital age.